How Does the Work Status Affect Employees' Job Attitude and Behavior in the Hotel Industry?. Issue 1 (2nd January 2017) - Lee, Hyung-Ryong; Kim, Kyungmi; Park, Seul Gi
Abstract: The study focuses on how work status impacts employees' perception of job satisfaction, organizational commitment, and job performance in the hotel industry. Also, it explores whether supervisors perceive employees' job attitudes and behavior in the same way as they perceive. Data were collected from a self-administered survey for five-star hotel employees and supervisors in Seoul, South Korea. A total of 335 valid responses were collected from 280 employees and 65 supervisors and analyzed by using structural equation modeling. The results of the study indicated that nonstandard employees expressed higher job satisfaction and higher organizational commitment but perceived lower job performance than standard employees did. Work status had no significant moderating effect on the relationships between job satisfaction, organizational commitment, and job performance; however, the results of this study indicated that supervisors' perceptions of nonstandard employees' job satisfaction, organizational commitment, and job performance were quite different from those of the nonstandard employees themselves. This study suggests that hotel operators should develop strategies to fully utilize nonstandard employees who reveal potential for quality service to guests.